PENGEMBANGAN MODEL SISTEM PENDIDIKAN INTEGRATIF DALAM PERSPEKTIF SISTEM PENYELENGGARAAN PENDIDIKAN - Repi Arianto; Didi Kosmanto; Wawan Herianto; Murniyanto; Muhammad Istan; Beni Azwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of globalization, digital technology transformation, and changes in societal needs demand the development of adaptive and innovative educational system models. This study aims to analyze the concept of systems in educational implementation and to develop an integrative educational system model relevant to the challenges of modern education. The study employed a qualitative approach using a library research method through the review of various SINTA-indexed national scientific journals and related educational literature. The results indicate that the educational system is an open system consisting of input, process, output, and outcome components that interact dynamically. The development of an integrative educational system model needs to consider aspects of educational policy, educational management, adaptive curriculum, technology-based learning, and collaboration with industry and society. The integrative educational system model developed in this study emphasizes the importance of synergy among educational components in improving the quality of educational implementation sustainably. Therefore, the development of an integrative educational system model can serve as a strategic alternative in improving the quality of competitive human resources in the era of globalization